Studies in medieval Jewish intellectual and social history : festschrift in honor of Robert Chazan - Chazan, Robert.; Wolfson, Elliot R.; Schiffman, Lawrence H.; Engel, David. (Supplements to The Journal of Jewish Thought and Philosophy, 2012)
For more than four decades Robert Chazan has been a copious source of original insights into the history and culture of medieval European Jewry, challenging conventional wisdom with profound erudition and sober analysis. In this volume, thirteen leading Judaicists and medievalists engage subjects that have been of particular concern to Professor Chazan during his distinguished career: the history of the Jewish communities in Western Christendom during the Middle Ages, Jewish-Christian interactions in medieval Europe, medieval Jewish Biblical exegesis and religious literature, and historical representations of the experience of medieval Jewry. Taken together they offer a comprehensive portrait of the state of the field of medieval Jewish studies.